Association between tobacco product use and asthma among US adults from the Population Assessment of Tobacco and Health (PATH) Study waves 2–4. Issue 1 (7th February 2023) - Brunette, Mary F; Halenar, Michael J; Edwards, Kathryn C; Taylor, Kristie A; Emond, Jennifer A; Tanski, Susanne E; Woloshin, Steven; Paulin, Laura M; Hyland, Andrew; Lauten, Kristen; Mahoney, Martin; Blanco, Carlos; et al.
Abstract : Background: Research on cigarettes and adult asthma offers mixed findings, perhaps due to overlap with chronic obstructive pulmonary disease (COPD) and inadequate adjustment for other smoke exposures. Associations between other tobacco products, including e-cigarettes, and asthma are also understudied. Research question: Using Population Assessment of Tobacco and Health Study waves 2–4 (2014/2015–2016/2017) data, we assessed the relation between tobacco product use and asthma in persons unlikely to have COPD. Study design and methods: Prospective study of 10 267 adults aged 18–39 years without COPD diagnoses. Past-month tobacco use at wave 2 was modelled first as combustible versus non-combustible use and second as specific product categories (former, cigarettes, e-cigarettes, cigars, hookah, smokeless tobacco). Outcomes included lifetime asthma prevalence at wave 2, incidence (waves 3 and 4) and Asthma Control Test score (lower=worse). Multivariable regressions adjusted for predictors of asthma, including other smoke exposures: cigarette pack-years, secondhand smoke and marijuana use. Sensitivity analyses examined findings when persons >39 years and those with both COPD and asthma were added, and when smoke exposure adjustments were removed. Results: No product, including cigarettes and e-cigarettes, was associated with prevalence or incidence of asthma. Among people with asthma at wave 2, combustible tobacco (beta=−0.86, 95% CI (−1.32 to –0.39)) and cigarettes (beta=−1.14, 95% CI (−1.66 to –0.62)) were associated with worse asthma control. No tobacco product was associated with asthma control over time. In sensitivity analyses, tobacco use became associated with incident asthma as adults >39 years and those with asthma+COPD were added, and as adjustments for other smoke exposures were omitted. Interpretation: Although cigarette use was associated with worse asthma control, there were no longitudinal associations between combustible tobacco or e-cigarette use and new onset or worsening asthma in these preliminary analyses. Research on tobacco and asthma should exclude COPD and adjust for smoking history and other smoke exposures.